Review on Li‐Sulfur Battery Systems: an Integral Perspective. Issue 16 (4th May 2015) - Rosenman, Ariel; Markevich, Elena; Salitra, Gregory; Aurbach, Doron; Garsuch, Arnd; Chesneau, Frederick Francois
<x xml:space="preserve">Abstract</x> The development and commercialization of Li ion batteries during recent decades is one of the great successes of modern electrochemistry. The increasing reliability of Li ion batteries makes them natural candidates as power sources for electric vehicles. However, their current energy density, which can reach an average of 200 Wh kg−1 on the single cell level, limits the possible driving range of electric cars propelled by Li‐ion batteries. Thereby, there is a strong driving force to develop power sources technologies beyond Li‐ion batteries that will mark breakthroughs in energy density capabilities. Li‐sulfur batteries have high theoretical energy density that can revolutionize electrochemical propulsion capability. Consequently, in recent years there has been much work throughout the world related to these systems. The scope of work on this topic justifies frequent publications of review articles that summarize recent extensive work and provide guidelines and direction for focused future work. Here, a comprehensive, systematic work related to Li‐sulfur battery systems is described, beginning with the Li anode challenges, carbon‐encapsulated sulfur cathodes, and various kinds of relevant electrolyte solutions. Based on the work described and parallel recent studies by other groups, important and comprehensive guidelines for further research and development efforts in this field are provided.